Targeted next-generation sequencing using bronchoalveolar lavage fluid samples for diagnosing pulmonary infections: a single-center retrospective study - Huang, Jinbao; Ye, Ling; Weng, Heng; Jiang, Meiqin; Lin, Ying; Li, Hongyan; Xie, Baosong (Frontiers in Microbiology, 2025)
ObjectivesTo evaluate the diagnostic value of targeted next-generation sequencing (tNGS) of bronchoalveolar lavage fluid (BALF) samples from patients with pulmonary infections (PIs).MethodsThis retrospective study included 110 patients diagnosed with suspected PIs, who underwent tNGS of BALF samples between February 2023 and January 2025. Conventional microbiological tests (CMTs), traditional culture, and tNGS were simultaneously performed, and the diagnostic efficiencies of the three PI methods were compared.ResultsA total of 110 BALF samples were obtained from 110 patients, including 80 with PIs and 30 without PIs. The detection sensitivities of tNGS, culture, and CMTs for the diagnosis of PIs significantly differed (P < 0.001). Further analysis showed that the sensitivity of tNGS was higher than those of culture (P < 0.001) and CMTs (P = 0.003). The specificity of the culture was higher than those of tNGS (P < 0.001) and CMTs (P < 0.001). However, the accuracy of culture was lower than those of tNGS (P < 0.001) and CMTs (P = 0.022), and the accuracy of CMTs was lower than that of tNGS (P = 0.022). Additionally, the area under the receiver operating characteristic curve for tNGS was better than that for CMTs (0.627 vs. 0.510). Among all causative pathogens, the bacteria were the most prevalent ones, of which the most commonly detected pathogens were Streptococcus pneumoniae (15.2%, 10/66), Pseudomonas aeruginosa (13.6%, 9/66), atypical pathogens (including Chlamydia psittaci, Chlamydia pneumoniae, and Mycoplasma pneumoniae) (13.6%, 9/66), Haemophilus influenzae (10.6%, 7/66), Klebsiella pneumoniae (10.6%, 7/66), and Mycobacterium tuberculosis complex (10.6%, 7/66). The most commonly detected fungi were Pneumocystis jirovecii (40.0%, 4/10) and Aspergillus (40.0%, 4/10), and the most commonly detected viruses were influenza virus A/B (55.6%, 10/18), and severe acute respiratory syndrome coronavirus-2 (27.8%, 5/18). The BALF tNGS results led to changes in the clinical plans of 50 (45.5 %) patients. However, the existing clinical management protocol was maintained in 28 patients (25.5 %) because the tNGS results supported the current diagnosis and management. Additionally, 32 (29.1 %) patients underwent adjustment of the clinical regimen or an unchanged clinical regimen based on empirical judgment and/or CMT results.LimitationsThis study had certain limitations, such as its retrospective design, relatively low specificity, and difficulty in identifying colonizing microorganisms. Through forward-looking in-depth research, the continuous accumulation of clinical experience, or the integration of artificial intelligence, tNGS will enable more precise and efficient management strategies for PIs.ConclusionThe sensitivity and accuracy of tNGS were better than those of culture and CMTs. tNGS results were critically associated with the development of clinical treatment plans for most patients. tNGS can be used as a rapid and accurate auxiliary diagnostic method, along with CMTs, for PIs.